Upaya Penanganan Seks Pada Anak Usia Dini Dalam Perspektif Kristen - Bu'ulolo, Berkati (Indo Green Journal, 2024)
The occurrence of sex is very noteworthy for the community, especially in the lives of children to distinguish what is good to do and what is not good to do. Sexual harassment is an act that can damage the psychological and physical well-being of children. The purpose of this study is to provide an explanation of efforts in handling the occurrence of sex in early childhood in a Christian perspective. This research method uses a descriptive qualitative method with data review from case studies, literature studies, and books as reference references. The result of this research is that in preventing sex in early childhood, the role of teachers and parents is needed in providing guidance on how to instill an attitude of self-awareness, instill an attitude of self-mastery, instill healthy friendships, instill an attitude of respect for privacy, provide an understanding of body boundaries in early childhood.